Evaluasi Penyerapan Kadar Logam Pada Daun Tanaman Wetland Pasca Pengolahan Limbah Cair Tenun - Hidayat, M. Gegas Imamuna Al; Fajri, Joni aldilla; Wulandari, Dewi (LPPM Universitas Mataram, 2024)
Water pollution can be caused by an increase in the number of industries, one of which is the textile industry. One effort to reduce water pollution by heavy metals is by utilizing absorption by plants. This research aims to determine the concentration of metal pollutants Cr, Cu, Cd, and Pb accumulated by Vetiveria zizanioides plants. The test method in this research was wet digestion using a nitric acid solution (HNO3) which was then analyzed using an Atomic Absorption Spectrophotometer (AAS). Based on research results, the average metal absorption concentration of copper (Cu), chromium (Cr), Lead (Pb), and cadmium (Cd) after processing using the FTW system with the help of bacteria in processing the highest metal content is Pb 0.0007 (mg /Kg dry weight) and for Cu it is 0.0001 (mg/Kg dry weight) and Cd metal is 0.00002 (mg/Kg dry weight) and finally Cr is 0.000001 (mg/Kg dry weight). And for processing using the FTW system without the help of bacteria in processing, the average metal absorption concentration of Cu, Cr, Pb, and Cd, the highest metal content at Cu 0.0001 (mg/Kg dry weight) and Pb 0.0003 (mg/ Kg dry weight) for Cr and Cd were not detected. The absorption of Cu, Cr, Pb, and Cd metals did not affect plant growth.